a) х^2 + xy - x - ax + a - a = x^2+ xy - x - ax = x( x + y ) - x( 1 + a )
b) x^2 - 3x -x + 3 +3x -5 = x^2 - x - 2
d = 1 + 4*2 = 9
x_1 = (1 - 9) / 2 = -2 / 2 = -1
x_2 = (1 + 3) / 2 = 4 / 2 = 2
D(f)∈(-∞;∞)
Асимптот нет,непериодическая
f(-x)=-x³+12x=-(x³-12x)
f(x)=-f(-x) нечетная
x=0 y=0
y=0 x(x²-12)=0 x=0 x=2√3 x=-2√3
(0;0);(2√3;0);(-2√3;0)-точки пересечения с осями
f`(x)=3x²-12=3(x-2)(x+2)=0
x=2 x=-2
+ _ +
(-2)(2)
возр max убыв min возр
уmax=-8+24=16
ymin=8-24=-16
f``(x)=6x=0
x=0 y=0
(0;0)-точка перегиба
- +
(0)
выпукл вверх вогнута вниз